METHOD OF VARIABLE INDEXING OF THE LEVEL OF CONFIDENTIALITY AND PROTECTION OF PERSONALIZED DATA IN TELECOMMUNICATION SYSTEMS AND NETWORKS - RUDYI, ROMAN; HRES, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article provides a comprehensive analysis of modern methods of storing personalized digital data and their classification by device types and architectural features. The main approaches to organizing information storage systems are considered, taking into account the requirements for security, reliability, and efficiency of hardware resource use. The architecture and generalized model of a data storage device are proposed, focused on ensuring multi-level access to confidential information. The choice of data representation format and methods for their protection is justified. The modeling confirmed the possibility of solving a number of practically important tasks, in particular, the analysis of information protection requirements according to the main criteria of information security: confidentiality, integrity, and availability. The proposed approach allows for the classification of personal data depending on their level of importance and requirements for timeliness of access, as well as determining the appropriate access levels and storage periods. This, in turn, ensures optimization of the use of system hardware resources and increases the efficiency of personal information accumulation processes. The developed application is of a demonstration nature and serves as confirmation of the operability of the proposed model. Further research should be directed towards developing methods for automated sorting of personal data according to specific criteria, as well as implementing the analyzed approaches using software and hardware reconfigurable resources, which will increase the flexibility and scalability of data storage systems.